2019
DOI: 10.1016/j.jtcvs.2018.10.155
|View full text |Cite
|
Sign up to set email alerts
|

Long-term experience with valve-sparing reimplantation technique for the treatment of aortic aneurysm and aortic regurgitation

Abstract: Objective: To analyze our long-term experience with valve-sparing reimplantation technique for the treatment of isolated root aneurysm, aneurysm with significant aortic regurgitation, and for isolated aortic regurgitation.Methods: Between 1999 and 2017, 440 consecutive patients underwent valvesparing reimplantation in our institution. The mean age of this cohort was 49 AE 15 years. Time-to-event analysis was performed with the Kaplan-Meier method, whereas significant predictors of late outcomes were explored w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 29 publications
8
57
2
1
Order By: Relevance
“…Their results demonstrated that independent of the status of the root and degree of aortic valve disease, VSRR could be performed safely and with excellent long-term durability. 3 These results attest to the beauty of the VSRR, or the David procedure, and merit publication both for dissemination of the results as well as a tribute to the work of the El Khoury group and the vision of David and Feindel. 4 Of interest are the 76 patients in the third, nonconventional group.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Their results demonstrated that independent of the status of the root and degree of aortic valve disease, VSRR could be performed safely and with excellent long-term durability. 3 These results attest to the beauty of the VSRR, or the David procedure, and merit publication both for dissemination of the results as well as a tribute to the work of the El Khoury group and the vision of David and Feindel. 4 Of interest are the 76 patients in the third, nonconventional group.…”
mentioning
confidence: 76%
“…In this study from the Belgium group led by El Khoury, the results from 440 valve-sparing root replacements (VSRRs) were reviewed. 3 The group was subdivided into 3 cohorts related to the traditional indications for VSRR: conventional for treatment of root aneurysms without aortic valve disease, debated for root aneurysms with aortic valve disease, and nonconventional for aortic valve disease when a root aneurysm is not involved. Their results demonstrated that independent of the status of the root and degree of aortic valve disease, VSRR could be performed safely and with excellent long-term durability.…”
mentioning
confidence: 99%
“…In this cohort, the early mortality was 1.2% and the overall survival at 10 and 15 years was 89.5 ± 2.0% and 77.9 ± 3.9%, respectively. In a recent study, Mastrobuoni et al [5] reported the long-term experience in 440 consecutive patients (mean age, 49 years; mean follow-up of five years; completeness of follow-up was 78%.) with aortic root aneurysm undergoing the reimplantation technique and a high number of associated ACR procedures (72.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a high percentage of the patients (83.9%) for type II AR dysfuntion underwent free-margin central plication as the most simple, reproducible, and efficient technique in case of cusp prolapse repair [3, 5].…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar results have been reported by Lansac's and El Khoury's groups for bicuspid and tricuspid valves. 12,13 VSRR is a very promising technique, and it is becoming more and more standardized. Its systematic application in the case of aortic root aneurysm with a reparable valve represents the ideal solution, especially for young patients with long life expectancy.…”
mentioning
confidence: 99%